Does coping strategies have asignificant relationship with quality of life among caregivers of chronic illness patients? - Aren, Merican; Rahim, Nurlatifah; Kasuma, Jati (COUNS-EDU: The International Journal of Counseling and Education, 2017)
The present study aimed to investigate the coping strategies and quality of life among caregivers of chronic illness patients. The study was conducted among the caregivers from five (5) villages in Sibu District of Sarawak by using a survey research design. A total of sixty seven (67) participants were participated in this study. Two different instruments were used to measure different types of variables. Research data collected was tested and analyzed by using a descriptive statistic and Pearson Correlation. The result revealed that there was a significant relationship between the coping strategies and the quality of life among caregivers of chronic illness patients. The relationship between both coping strategies and domains of quality of life was in a moderate level.  As an implication, counselors should be more aware about the types of coping strategies used by the caregivers because it can affect the individual’s quality of life indirectly.